Impact of timing and precision of histopathological diagnosis on outcomes of patients with Burkitt lymphoma and high‐grade B‐cell lymphoma. (2nd February 2022) - Graef, Claus Moritz; Gödel, Philipp; Falderbaum, Philipp; Balke‐Want, Hyatt; Simon, Florian; Sieg, Noëlle; Naendrup, Jan‐Hendrik; Neumann, Marie Anne‐Catherine; Gillessen, Sarah; Bröckelmann, Paul J.; Eichenauer, Dennis A.; Borchmann, Peter; et al.
Abstract: Background: Burkitt lymphoma (BL) and diffuse large B‐cell lymphoma (DLBCL) are aggressive B‐cell non‐Hodgkin lymphomas (B‐NHL) with a generally favorable prognosis after immunochemotherapy. The outcome of BL is superior to DLBCL. In 2016, a distinct group of lymphomas displaying characteristics of both BL and DLBCL (high grade B‐cell lymphoma, HGBL) was introduced into the WHO classification. Histopathological discrimination of BL, DLBCL, and HGBL may be challenging. Data on the frequency of histopathological difficulties resulting in revision of the final diagnosis of BL/DLBCL/HGBL and its impact on the prognosis are limited. Methods: We assessed histopathological features and clinical outcomes of 66 patients with suspected diagnosis of BL at the reporting institution between 2010 and 2020. Results: The median age was 51 years (range 19‐82) and final histopathological diagnosis revealed BL (n = 40), DLBCL (n = 12), or HGBL (n = 14). Patients with DLBCL and HGBL were either treated with DLBCL‐directed (83.3% and 35.7%) or BL‐directed (16.7% and 64.3%) protocols. Patients in whom diagnosis was revised from DLBCL to BL after initiation of DLBCL‐directed treatment had a significantly inferior progression‐free survival (PFS) than patients initially diagnosed with BL (p = 0.045), thus resembling rather the prognosis of DLBCL/HGBL. There was no difference between patients with DLBCL and HGBL, respectively, regarding PFS and OS (p = 0.38 and p = 0.27). Conclusion: These results suggest that timely and precise histopathological diagnosis as well as reference histopathological review of the underlying lymphoma is critical to determine up‐front treatment strategies. Consequently, selection of more aggressive treatment protocols in case of difficulties with discrimination between DLBCL/HGBL/BL may be a reasonable approach.